EFFECT OF LOW INTENSITY PULSED ULTRASOUND ON REPAIR OF TENOTOMIZED ACHILLES TENDON OF RABBIT - Saddam Khalid Humadi; Hiba Abdulaziz Shekho (Basrah Journal of Veterinary Research)
Tenotomized Achilles tendon Rabbits were used to investigate the effect of lowintensity pulsed ultrasound (LPUS) to accelerate the repair of injured tendon. The medial Achilles tendons of 18 local breed male rabbits were transected of all animals without suture, and bandaging was performed to immobilization the injured limb. Nine animals were chosen randomly to receive low-intensity pulsed ultrasound, the other 9 animals served as control. pulsating ultrasound with intensities 500 mW/cm2 and frequency 2.5 MHz were given over the healing tendons for 10 minute daily, using a gel as the coupling agent between the ultrasound probe and the skin. The healing tendons were evaluated clinically, macroscopically and microscopically for three periods at 7, 14 and 21 days respectively after tenotomy, three rabbits for each period. In the ultrasound-treated group at 14 and 21 days postoperatively, the macroscopic and histological studies demonstrated that the low-intensity pulsed ultrasound enhanced the healing of tendomize Achilles tendon. The ultrasound treated group showed more mature organization at all end points of injured tendons compared